INFORMANTS ANONYMOUS (IA) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2009)
Jonathan Schwartz is dealing with the problem of anonymity in anthropological research asking: why is the falsification imperative so important in anthropological “ethics”? Anonymity is considered as a norm in the contemporary anthropological research when disguising the true identity of informants is practiced even when there is no obvious reason for it.
Keywords: informants; anonymity; anthropology; fieldwork